A Study of EFL Students‘ Awareness on Apology through Cross Cultural Learning Activities - Ardiyani Widya Permatasari; Diah Kristina; Sumardi Sumardi (EDULANGUE, 2018)
This study was aimed at exploring what types of cross cultural learning activities used that contribute to EFL students’ awareness on apology function, and how the process occurred at an EFL tertiary level. The data analyzed in this study were collected in Satya Wacana Christian University and Sebelas Maret University. The study was a mixed method in nature using a questionnaire and interview adapted from previous studies. The quantitative data was obtained from six Indonesian EFL students using Discourse Completion Tasks Questionnaires (DCTQ), while the qualitative data obtained from individual interviews carried out with six EFL students. The results showed that there were group discussion and role playing used as cross cultural learning activities which contributed to EFL students’ awareness on apology functions. Another finding also indicated the use of apology strategies performing those two learning activities. It was unveiled that that EFL students employed numerous apology strategies that they were well aware of how to use adequate apology forms to meet the requirement of certain situations and relationships, and that they felt the need for explaining and avoiding interpretation of their responses as an apology.